The influence of moving by trains on a designed building situated near the railway track as well as on technical devices and people in the building - Gnyp, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
An accelerated development of urban communication infrastructure, especially that of railway, forces search for new space for investment. The area of communication infrastructure interpenetrates usable space creating mutual symbiotic interaction. This development carries the growth of influence on the surrounding areas. This article presents the influence of a railway infrastructure on a newly designed commercial and office center situated on the flyover over the railway track, as well as on technical devices and people staying there. The aim of the research and the analysis was to gain information about acceleration spectrum of the response of the building that is situated near the railway track and thus to forecast vibration timings of a designed building together with kinematic excitation at the level of foundation. For static strength calculations, the research investigated the influence of subsoil vibrations caused by rolling stock on a dynamic stress increase in the structure as well as on the specification of a dynamic factor and thus on taking into consideration the growth and stress variation in design approach. The analysis of the dynamic factor at the designing level enables us to eliminate the influence of vibration exposure by introducing vibration damping system in the most optimal location of vibration centre.